The impact of the organisational environment on leadership style : a study of the hotel industry - Ng, Puay Leng (2015)
This report reviewed prior studies that focus on environmental impact of leadership or managerial behaviour. Our survey shows that managers, on the whole, recognise the environmental ramifications of their style in leading their subordinates. In addition, various dimensions of the environment in which they operate give rise to a particular style. The dimensions of the environment studied are degree of complexity, degree of dynamism and degree of hostility. The findings show that, in reality, managers in highly complex and dynamic environment are more likely to be autocratic. However, in a hostile situation, they are more likely to be empathetic towards their subordinates, therefore they are inclined towards a laissez-faire or shared leadership style.